Modified triglyceride-glucose index indices are reliable markers for predicting risk of metabolic dysfunction-associated fatty liver disease: a cross-sectional study - Kim, Ae Hee; Son, Da-Hye; Lee, Yong-Jae (Frontiers in Endocrinology, 2024)
Metabolic dysfunction-associated fatty liver disease (MAFLD) is newly proposed nomenclature, and its diagnosis involves an algorithm that can be complicated and impractical for clinicians in real-world clinical settings. Thus, we investigated the association between MAFLD and modified triglyceride-glucose index (TyG) indices to find a more concise, feasible method for predicting MAFLD in everyday clinical care.Data were obtained from people who voluntarily underwent health check-ups at the Health